Sargramostim (rhu GM-CSF) as Cancer Therapy (Systematic Review) and An Immunomodulator. A Drug Before Its Time? - Lazarus, Hillard M.; Ragsdale, Carolyn E.; Gale, Robert Peter; Lyman, Gary H. (Frontiers in Immunology, 2021)
Background Sargramostim (recombinant human granulocyte-macrophage colony-stimulating factor [rhu GM-CSF]) was approved by US FDA in 1991 to accelerate bone marrow recovery in diverse settings of bone marrow failure and is designated on the list of FDA Essential Medicines, Medical Countermeasures, and Critical Inputs. Other important biological activities including accelerating tissue repair and modulating host immunity to infection and cancer via the innate and adaptive immune systems are reported in pre-clinical models but incompletely studied in humans. Objective Assess safety and efficacy of sargramostim in cancer and other diverse experimental and clinical settings. Methods and Results We systematically reviewed PubMed, Cochrane and TRIP databases for clinical data on sargramostim in cancer. In a variety of settings, sargramostim after exposure to bone marrow-suppressing agents accelerated hematologic recovery resulting in fewer infections, less therapy-related toxicity and sometimes improved survival. As an immune modulator, sargramostim also enhanced anti-cancer responses in solid cancers when combined with conventional therapies, for example with immune checkpoint inhibitors and monoclonal antibodies. Conclusions Sargramostim accelerates hematologic recovery in diverse clinical settings and enhances anti-cancer responses with a favorable safety profile. Uses other than in hematologic recovery are less-well studied; more data are needed on immune-enhancing benefits. We envision significantly expanded use of sargramostim in varied immune settings. Sargramostim has the potential to reverse the immune suppression associated with sepsis, trauma, acute respiratory distress syndrome (ARDS) and COVID-19. Further, sargramostim therapy has been promising in the adjuvant setting with vaccines and for anti-microbial-resistant infections and treating autoimmune pulmonary alveolar proteinosis and gastrointestinal, peripheral arterial and neuro-inflammatory diseases. It also may be useful as an adjuvant in anti-cancer immunotherapy.